2022
DOI: 10.3390/cancers14184523
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy and Hepatocellular Cancer: Where Are We Now?

Abstract: Immunotherapy has demonstrated its effectiveness in many cancers. In hepatocellular carcinoma (HCC), promising results shown in the first phase II studies evaluating anti-PD-1 or anti-PD-L1 monotherapies resulted in their approval in the United States. Approval was not obtained in Europe; subsequent randomized studies in first- or second-line treatment did not confirm these initial results. However, first data with immunotherapy plus antiangiogenic treatments or dual immunotherapy combinations were positive. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 71 publications
0
1
0
Order By: Relevance
“…The results of this study predict several behaviors that have been clinically observed. Supplementary Figure S4 revealed that the benefit of adding Y90-RE to ICIs is increasingly improved in both targeted and non-targeted tumors than in patients who have only received a single treatment, as shown by previously small retrospective clinical trials [20,24,25]. The benefits of adding Y90-RE to ICIs are progressively enhanced in patients where less disease is left untreated.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…The results of this study predict several behaviors that have been clinically observed. Supplementary Figure S4 revealed that the benefit of adding Y90-RE to ICIs is increasingly improved in both targeted and non-targeted tumors than in patients who have only received a single treatment, as shown by previously small retrospective clinical trials [20,24,25]. The benefits of adding Y90-RE to ICIs are progressively enhanced in patients where less disease is left untreated.…”
Section: Discussionmentioning
confidence: 58%
“…The yttrium 90-radioembolization (Y90-RE) can stimulate the release of tumor antigens, which can activate T cells and enhance anti-tumor immunity [17], induce immunogenic cell death resulting in tumor regression in distant non-irradiated areas [18,19], and change the tumor microenvironment [20]. As Y90-RE has been shown to activate the immune system, further investigations are needed to evaluate the effectiveness and safety of Y90-RE and ICI combination treatment for HCC patients [21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 46 , 47 As the emergence of new multi-kinase inhibitors, immunotherapy, and the combination of the two, sorafenib was not the first choice for HCC patients worldwide. 48 , 49 However, we believe that our study could be applied not only for the sorafenib, but also for other multi-kinase inhibitors as Lenvatinib, and atezolizumab and bevacizumab.…”
Section: Discussionmentioning
confidence: 99%
“…The IMbrave150 study demonstrated a one-year survival rate of 67.2% with Ate/Bev compared to 54.6% with sorafenib [4]. Therefore, Ate/Bev therapy is recommended as the first-line therapy for advanced HCC, including for patients with portal vein tumor thrombosis (PVTT) [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%